A new analytical approach to study chaos fraction characterization by using intensity interferometry. (November 2021) - Bary, Ghulam; Ahmed, Waqar; Sajid, Muhammad; Ahmad, Riaz; Khan, Ilyas; Huang, Duohui; Wang, Yue
Highlights: Chaotic behavior is discussed in investigating the characteristics of the particle emitting sources. We have calculated the coherence and chaos fraction in the evolving pion gas model with Bose-Einstein condensation. The relationship between the source temperature and momentum has been discussed with relativistic hydrodynamics. Consequences of the temperature and momentum have been described. We have analyzed the strength of the correlations in terms of the weight factors to explore the chaos and coherence fractions. Abstract: Multi particle intensity correlations measured to investigate the fluid debris produced during the collisions at the world largest colliders and observed a remarkable suppression in the measurement of three and four pions interferences. The analogous suppression can be analyzed to explore the chaos and coherence fractions of particle production sources in the collisions of heavy nuclei at unprecedented energies. We illustrate and explore the particles emissions from radiated sources with Bose Einstein coherence which induce multi particle interferences to probe the peculiarity of the sources as well as the distinctions about the chaos fraction in the collisions at unrivalled energies. We perspicacious that pions seem to the pertinent aspirant of coherence and chaos fractions, and the normalized chaos weight factors evaluate the existence of such hybrid phases of chaos and coherence significantly. The key point of this research is that we analyze normalized chaos weight factors to examine the chaos and coherence fractions of pions during the collisions of heavy nuclei. With such distinctive and novel approach, we observe a significant difference in the normalized chaos weight factors at small temperature and large momenta regimes.